Arquitetura da participaç\~ao no Brasil: Uma leitura das representaç\~oes políticas em espaços participativos nacionais - Ana Claudia Chaves Teixeira; Clóvis Henrique Leite de Souza; Paula Pompeu Fiuza Lima (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The paper points the characterization of different logics of political representation present at national conferences and councils. Based on the analysis of what is provided of decrees and laws that define how it should operate the representative dynamic in national councils and conferences, one realizes that the main theoretical approaches of representation used to study representative institutions by nature and spaces of mediation of interests can be applied to participatory spaces. The discussion about the objectives of these spaces, how to choose the participants and the categories of participants involved indicate that before participatory they are representative spaces, because they face similar challenges of Parliaments and Executive in regard to representation and responsiveness.
Keywords: Z18; 330; democracy; participation; representation; participatory spaces; councils; conferences